(3GdbGfhfs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg hGdUdGI Ydi YHGOg GdeDefjf hEP bO hajfG hYOfG ef JUfja cJHfG ai GdWH hMGf dfG Cf fPcQ ai gPG GdcJGH GdQGHY GdCeQGV GdJi dG jNJU HYVh HYjfg s
(3BNQgG (B:s
(3CUGHY GdQLd YdGLgG ai GdcSQ hGdNdY YdGL CUGHY GdjO , hQHeG ShGgG GdeLHQ HbOeg Je Gdaf GdNGeS ef GdcJGH GdQGHY hGdMeO ddg s
(3JTJed Ydi GdcJGH GdQGHY GdNGU HGdCeQGV GdLRFjI GdJi EPG hbYJ de JNJU HYVhs
(3fSNI SGOSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs